Influence of dehydrated wheat/rice cereal matrices on probiotic activity of Bifidobacterium animalis ssp. lactis BB-12® - Leboš Pavunc, Andreja (Array, 2019)
Three novel dehydrated wheat/rice cereal functional products with an addition of well documented probiotic Bifidobacterium animalis ssp. lactis BB-12® (BB-12®) were developed in Podravka factory for the infants older than 4 months: instant rice cereal, instant rice cereal with fruits and instant wheat cereal with vanilla. Notably, the number of viable BB-12® cells in each of the novel products was higher than the required minimal number of probiotic cells per gram of product (106 CFU/g) during the storage period of 106 weeks. Therefore, BB-12® strain recovery and genome stability were evaluated by strain-specific polimerase chain reaction and amplified fragment length polymorphism fingerprinting analysis. Further aim was to evaluate the influence of these three different cereal food matrices on specific probiotic properties of BB-12® strain in vitro. Applied food matrices positively influenced the survival in the simulated conditions of the gastrointestinal tract and antagonistic activity against undesirable microorganisms, while no influence on auto- and coaggregation ability of B. animalis ssp. lactis BB-12® was observed. Adhesion to extracellular matrix proteins and intestinal epithelial Caco-2 cells together with antibacterial activity emphasized competitive pathogen exclusion from Caco-2 cells by probiotic strain BB-12®.